Strengthening Local Wisdom through Pancasila Student Profile-Based PAI Learning for Muslim Students in Bali - Ma`arif, Muhammad Anas; Rugaiyah, Rugaiyah; Chalim, Saifuddin (At-tadzkir: Islamic Education Journal, 2025)
Education plays a central role in shaping students' character and competencies. Islamic Religious Education (PAI) serves as a means of fostering students' morals and religious understanding. However, its implementation in public schools faces several challenges, including limited instructional time and a lack of integration with daily life. With the implementation of the Merdeka Curriculum, the Pancasila Student Profile (P5) has become a foundation for character development. However, preliminary research indicates that teachers' understanding of P5 implementation in PAI learning remains limited.  This study aims to analyze the implementation of P5 values in PAI learning at SMP Negeri 2 Negara, focusing on strategies for internalizing values, challenges encountered, and recommendations for improving learning effectiveness. This research employs a qualitative approach with a case study method. The findings reveal that although various activities based on local wisdom have been implemented, the internalization of P5 values in PAI learning has not been optimal. The successful implementation of P5 values depends on contextual learning strategies, active teacher participation, and an inclusive school environment.  This study contributes to identifying challenges and opportunities in developing a more inclusive and diversity-based model of religious education. Therefore, a holistic approach to PAI learning is needed to ensure that Islamic and Pancasila values are deeply and sustainably instilled in students' lives.